Building Capacity dalam Pendidikan Anti Korupsi : Studi : Kebijakan Kurikulum Dinas Pendidikan Di Provinsi Aceh - Dyah Kuntorini; Aflia Rizki; Oki Satria; Nur Hafni (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
An educational institution's success depends on its anti-corruption approach. This study's goal is to explain how the Corruption Eradication Commission's (KPK) strategy can be used to incorporate anti-corruption values into the academic curriculum. This study employs library research, which is research whose research objectives are discovered using a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). According to the study, the Corruption Eradication Commission's (KPK) achievement in preventing and harshly punishing corrupt individuals on Indonesian soil is evidence of the effectiveness of the anti-corruption policy. Several alternative models that can be used to instill anti-corruption values in schools include models as separate subjects, integrated models in all subjects, models outside of the classroom, models of culture and habituation of values in all school activities and atmosphere, and finally the combined model.